Chronic exposure to environmentally relevant levels of simvastatin disrupts zebrafish brain gene signaling involved in energy metabolism. Issue 3 (1st February 2020) - Barros, Susana; Coimbra, Ana M.; Alves, Nélson; Pinheiro, Marlene; Quintana, José Benito; Santos, Miguel M.; Neuparth, Teresa
ABSTRACT: Simvastatin (SIM), a hypocholesterolaemic drug belonging to the statins group, is a widely prescribed pharmaceutical for prevention of cardiovascular diseases. Several studies showed that lipophilic statins, as SIM, cross the blood-brain barrier and interfere with the energy metabolism of the central nervous system in humans and mammalian models. In fish and other aquatic organisms, the effects of SIM on the brain energy metabolism are unknown, particularly following exposure to low environmentally relevant concentrations. Therefore, the present study aimed at investigating the influence of SIM on gene signaling pathways involved in brain energy metabolism of adult zebrafish ( Danio rerio ) following chronic exposure (90 days) to environmentally relevant SIM concentrations ranging from 8 ng/L to 1000 ng/L. Real-time PCR was used to determine the transcript levels of several genes involved in different pathways of the brain energy metabolism ( glut1b, gapdh, acadm, accα, fasn, idh3a, cox4i1, and cox5aa ). The findings here reported integrated well with ecological and biochemical responses obtained in a parallel study. Data demonstrated that SIM modulates transcription of key genes involved in the mitochondrial electron transport chain, in glucose transport and metabolism, in fatty acid synthesis and β-oxidation. Further, SIM exposure led to a sex-dependent transcription profile for some of the studied genes. Overall, the present study demonstrated, for the first time, that SIM modulates gene regulation of key pathways involved in the energy metabolism in fish brain at environmentally relevant concentrations.